(untitled) (International Journal of Engineering and Computer Science, 2017)
Identifying the characteristics and the originality of the any digital device has become more important in today’s digital world using digital forensics. This survey paper studies the recent developments in the field of image source identification. Proposed methods in the literature are divided into five broad areas based on source identification using Metadata (Exif), Image Features, CFA and Demos icing Artifacts, Lens Distortions and Wavelet Transforms. The methods and algorithm of the proposed approaches in each category is described in detail to use accurate technique in source camera identification.